Strategy of ILCA to improve productivity of pasture and forage resources in Africa - Peters, Kurt J.; Tothill, J.C. (1988)
Examines the role of forages and ILCA's strategy to improve productivity of forage resources for improving the stability and sustainability of African farming systems. Discusses constraints on African Farming Systems, Organization of research and integration of forages in two farming systems. Outlines genetic resources identification, evaluation and implementation.